Another Circular Circus Act!

Geometry Level 5

A circle of radius r r is positioned, so that it has two points of tangency with the ellipse x 2 25 + y 2 121 = 1 \dfrac{x^2}{25} + \dfrac{y^2}{121} = 1 . Two other circles, both of radius r r and in different quadrants, are positioned so that they are also tangent to the ellipse, the circle and the x x -axis.

If the value of the r r can be expressed as a b \dfrac{a}{b} , where a a and b b are coprime positive integers, input a + b a + b as your answer.

Inspiration.


The answer is 442.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Feb 17, 2021

Let the centers of the middle circle and the right circle be O O and Q Q respectively, and the tangent point of the two circles with the ellipse be P ( u , v ) P(u,v) . Note that O P = P Q = r OP=PQ = r . Since the x x -coordinate of P P is u u , that of Q Q is 2 u 2u .

The line (red) joining O O , P P , and Q Q is given by y v x u = m \dfrac {y-v}{x-u} = m , where m m is the gradient of the line which is perpendicular to the tangent of the ellipse at point P P . The gradient of the tangent to the ellipse is given by

2 x 25 + 2 y 121 d y d x = 0 d y d x = 121 x 25 y \dfrac {2x}{25} + \dfrac {2y}{121} \cdot \dfrac {dy}{dx} = 0 \implies \dfrac {dy}{dx} = - \dfrac {121 x}{25 y}

The gradient of the tangent at point P ( u , v ) P (u,v) is 121 u 25 v - \frac {121 u}{25 v} and therefore m = 25 v 121 u m = \frac {25 v}{121 u} and the equation of the red line is given by y = 25 v 121 u x + 96 121 v y = \dfrac {25 v}{121 u}x + \dfrac {96}{121} v . Then O = ( 0 , 96 121 v ) O = \left(0, \frac {96}{121} v \right) and Q = ( 2 u , 146 121 v ) Q = \left(2u, \frac {146}{121} v \right) . We also note that:

{ u 2 + ( v 96 121 v ) 2 = u 2 + ( 25 121 ) 2 v 2 = r 2 v + 25 121 v = 146 121 v = r \begin{cases} u^2 + \left(v-\dfrac {96}{121}v \right)^2 = u^2 + \left(\dfrac {25}{121} \right)^2v^2 = r^2 \\ v + \dfrac {25}{121} v = \dfrac {146}{121} v = r \end{cases}

Therefore,

u 2 + ( 25 121 ) 2 v 2 = ( 146 121 ) 2 v 2 Since u 2 25 + v 2 121 = 1 25 25 121 v 2 + ( 25 121 ) 2 v 2 = ( 146 121 ) 2 v 2 23716 12 1 2 v 2 = 25 23716 v 2 = 366025 v = 55 14 r = 146 121 v = 365 77 \begin{aligned} \blue{u^2} + \left(\frac {25}{121} \right)^2v^2 & = \left(\frac {146}{121} \right)^2v^2 & \small \blue{\text{Since }\frac {u^2}{25} + \frac {v^2}{121} = 1} \\ \blue{25 - \frac {25}{121} v^2} + \left(\frac {25}{121} \right)^2v^2 & = \left(\frac {146}{121} \right)^2v^2 \\ \frac {23716}{121^2} v^2 & = 25 \\ 23716 v^2 & = 366025 \\ v & = \frac {55}{14} \\ \implies r & = \frac {146}{121} v = \frac {365}{77} \end{aligned}

Therefore a + b = 442 a+b = \boxed{442} .

David Vreken
Feb 16, 2021

Let the middle circle have a center of ( 0 , b (0, b ) so that its equation is x 2 + ( y b ) 2 = r 2 x^2 + (y - b)^2 = r^2 .

Substituting x 2 = r 2 ( y b ) 2 x^2 = r^2 - (y - b)^2 into x 2 25 + y 2 121 = 1 \cfrac{x^2}{25} + \cfrac{y^2}{121} = 1 and solving for y y gives y = 121 96 b ± 11 96 25 b 2 + 96 r 2 2400 y = \cfrac{121}{96}b \pm \cfrac{11}{96}\sqrt{25b^2 + 96r^2 - 2400} .

For the circle to be tangent to the ellipse, y y will only have one value, so 11 96 25 b 2 + 96 r 2 2400 = 0 \cfrac{11}{96}\sqrt{25b^2 + 96r^2 - 2400} = 0 , which solves to b = 4 5 150 6 r 2 b = \cfrac{4}{5}\sqrt{150 - 6r^2} , and y = 121 96 b y = \cfrac{121}{96}b .

Since the center of the outer circle has a y y -coordinate of r r , and since the tangent point between the ellipse and circle is the midpoint of the center of the middle circle and one of the outer circles, 1 2 ( b + r ) = 121 96 b \cfrac{1}{2}(b + r) = \cfrac{121}{96}b , or r = 73 48 b r = \cfrac{73}{48}b .

Substituting b = 4 5 150 6 r 2 b = \cfrac{4}{5}\sqrt{150 - 6r^2} into r = 73 48 b r = \cfrac{73}{48}b gives r = 73 48 4 5 150 6 r 2 r = \cfrac{73}{48} \cdot \cfrac{4}{5}\sqrt{150 - 6r^2} , which solves to r = 365 77 r = \cfrac{365}{77} .

Therefore, a = 365 a = 365 , b = 77 b = 77 , and a + b = 442 a + b = \boxed{442} .

Ameya Deshmukh
Feb 15, 2021

If we let the common tangency point in the first quadrant be ( 5 sin θ , 11 cos θ ) (5\sin\theta,11\cos\theta) ,

the slope of the normal at the point will be 1) 1 d y d x = 25 121 11 cos θ 5 sin θ = 5 11 tan θ = tan ϕ \frac{-1}{\frac{dy}{dx}}=\frac{25}{121}\frac{11\cos\theta}{5\sin\theta}=\frac{5}{11\tan\theta}=\tan\phi ,

Now, moving a distance r r to the right along the normal will make the ordinate = r =r

2) 11 cos θ + r sin ϕ = r 11\cos\theta + r\sin\phi=r

And, moving r r to the left we will end up on the y-axis, since the center of the middle circle has to lie there by symmetry.

3) 5 sin θ r cos ϕ = 0 5\sin\theta-r\cos\phi=0

Using the last 2 equations together and the first relation,

tan ϕ = r 11 cos θ 5 sin θ = 5 11 tan θ \tan\phi = \frac{r-11\cos\theta}{5\sin\theta}=\frac{5}{11\tan\theta} ,

This gives r = 146 cos θ 11 r=\frac{146\cos\theta}{11}

Substituting this in 2 gives,

cos θ = 5 14 \cos\theta=\frac{5}{14}

Therefore, r = 365 77 r=\frac{365}{77}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...